CO2-broadening and shift coefficients of sulfur dioxide near 4 µm. (March 2019) - Borkov, Yu.G.; Lyulin, O.M.; Petrova, T.M.; Solodov, A.M.; Solodov, A.A.; Deichuli, V.M.; Perevalov, V.I.
Highlights: CO2 -broadening and shift coefficients of the sulfur dioxide in the 4 µm region. Measured CO2 -broadening coefficients for SO2 are smaller than those from HITRAN2016. Mean value of the CO2 -shift coefficients for SO2 in the 4 µm region is −0.0027 cm −1 atm −1 . Abstract: The absorption spectra of the mixture of SO2 and CO2 at different partial pressures of both gases have been recorded at room temperature in the 4 µm region using the Bruker IFS 125 HR FTIR spectrometer. The multispectrum fitting procedure has been applied to these spectra to recover the CO2 -broadening and shift parameters of the sulfur dioxide spectral lines. The CO2 broadening and the pressure induced shift coefficients for 1422 and 116 lines of the ν1 + ν3 A -type band of 32 S 16 O2 and 34 S 16 O2, respectively, have been derived. Beside, these coefficients have been derived for 254 lines of the ν1 + ν2 + ν3 − ν2 hot band of 32 S 16 O2 . The rotational dependence of the values of these coefficients is discussed. The CO2 pressure induced shift coefficients for this molecule are published for the first time. The comparison of the obtained broadening coefficients to those published by other authors for one pure rotational line and for the lines of the ν1 B -type band is given.